PENGARUH METODE PEMBELAJARAN KOOPERATIF (COOPERATIVE LEARNING) TERHADAP HASIL BELAJAR SULAMAN PADA MATA PELAJARAN PRAKARYA KELAS X SMAN 9 PADANG - MUTIARA ZAHRATI, Dr.Ramalis Hakim, M.Pd. Dra. Ernis, M.Pd (Serupa The Journal of Art Education, 2015)
In this research, it studied about the effects of cooperative learningmethodson students’ embroidery learning out comeson craft subjectingrade X of SMAN 9 Padang. The purpose of this study was to determinewhether learning out comes in teaching embroidery by using cooperativelearning methods is higher than learning out comes by using conventionalmethods. To answer the problems above, this study used a quasiexperimental. The technique of data analysis was descriptive processing stage, the stages of inductive analysis processing which consists of; normality test and homogeneity test, and hypothesis testing stage by using adifferent test (Paired Samplet test).The results of the study showed that there are significant effects of cooperative learning methodson students’ learning out comes of craft subject ingrade X of SMAN 9 Padang. Based on the hypothesis test conducted thatthe tvalue =11.576 and ttable =2.040. This means that tvalue>ttable, then Ho is rejected it means that the average (mean) value of the experimental class and the control class are not identicalor different. It can be concluded that the use of cooperative learning gives positive effects on improving students learning out comes in grade X of SMA 9 Padang on craft subject.Kata kunci : hasil belajar, sulaman, mata pelajaran prakarya,metodepembelajaran kooperatif